Transformasi Komunikasi Antarbudaya di Perbatasan Indonesia–Timor Leste Melalui Media Sosial Facebook - Taka, Elvira Leonita; Andung, Petrus Ana; Nope, Hotlif Arkilaus; Konradus, Blajan; Dupe, Frengky (Fakultas Ilmu Komunikasi UKWMS, 2025)
The border communities of Indonesia and Timor Leste present intriguing social and cultural phenomena. The social relations between these border communities in both countries remain strong due to kinship ties and historical proximity, despite being separated by national administrative boundaries. The aim of this study is to analyze the cross-cultural communication patterns of the Indonesia-Timor Leste border communities through Facebook social media and to explore the meanings attached to digital interactions on social media by these communities. This qualitative research adopts an interpretive paradigm, employing a media ethnography methodology. Data collection was carried out through observations and in-depth interviews with community members, including youth, women, and community leaders. The findings indicate that social media has brought about a transformation in cross-cultural communication within the border communities, where Facebook has